Snow White - Phelan, Matt 1970- (Candlewick Press, 2016)
The scene: New York City. The dazzling lights cast shadows that grow ever darker as the glitzy prosperity of the Roaring Twenties screeches to a halt. Enter a cast of familiar characters: a young girl, Samantha White, returning after being sent away by her cruel stepmother, the Queen of the Follies, years earlier; her father, the King of Wall Street, who survives the stock market crash only to suffer a strange and sudden death; seven street urchins, brave protectors for a girl as pure as snow; and a mysterious stock ticker that holds the stepmother in its thrall, churning out ticker tape imprinted with the wicked words "Another ... More Beautiful ... KILL."
Keywords: Schneewittchen; Bearbeitung; USA; Stepmothers / Comic books, strips, etc; Depressions / 1929 / United States / Comic books, strips, etc; New York (N.Y.) / Comic books, strips, etc; Snow White (Tale) / Adaptations / Fiction; Fairy tales / Adaptations / Fiction; Depressions / 1929 / New York (State) / New York / Fiction; Manhattan (New York, N.Y.) / Fiction; JUVENILE FICTION / Comics & Graphic Novels; JUVENILE FICTION / Fairy Tales & Folklore / Adaptations; JUVENILE FICTION / Historical / United States / 20th Century; Heiresses / Comic books, strips, etc / Fiction; Stepmothers / Comic books, strips, etc / Fiction; New York County (N.Y.) / Fiction; Snow White (Tale) / Adaptations / Comic books, strips, etc; 1929; Graphic novels; Graphic novels / United States; Graphic novels / Juvenile; Historical comics; Noir comics; Fairy tales; Graphic novels, Juvenile; Comic; Jugendbuch